The Initial Assessment of Nurse Knowledge to Response Time in Traffic Accident Case - Nandang DD Khairari (Universitas Muhammadiyah Semarang, 2021)
The occurrence of patients with traffic accidents is increased so much that the nurses need to enhance the knowledge of the response time services in the service of traffic accident cases. This research is to define the relationship between the nurses’ knowledge level to the initial assessment of the nurses’ response time in the service of traffic accident cases in the emergency departments. The study was conducted in the emergency room of Dr R. Soedjono Selong Hospital. The study was quantitative with cross-sectional planning. Total sampling was used and obtained 25 respondents. The results showed that nurses' knowledge level is 80% categorized as well, 16% categorized as moderate and 4% categorized as low. For nurse response time, 96% categorized as fast and 4% categorized as slow. The statistical test was used the chi-square test with SPSS. The P-value is 0,000, which implies there is a relationship between nurse knowledge level to the initial assessment of the nurses’ response time in the service of traffic accident cases.